2014
DOI: 10.1007/s11892-014-0558-1
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Worker Interventions for Latinos With Type 2 Diabetes: a Systematic Review of Randomized Controlled Trials

Abstract: This systematic review aimed to synthesize glucose (HbA1c) outcomes of community health worker (CHW)-delivered interventions for Latinos with type 2 diabetes that were tested in randomized controlled trials and to summarize characteristics of the targeted populations and interventions, including the background, training, and supervision of the CHWs. Searches of PubMed and Google Scholar databases and references from selected articles identified 12 studies that met the inclusion criteria. Of these, seven report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 33 publications
(237 reference statements)
2
45
0
Order By: Relevance
“…Two recent reviews of CHW interventions found that some, but not all, randomized trials show benefit for HbA1c [29,30]. Our results may be due to the fact that stress management, rather than diabetes self-care per se, was the focus of the intervention.…”
Section: Discussionmentioning
confidence: 74%
“…Two recent reviews of CHW interventions found that some, but not all, randomized trials show benefit for HbA1c [29,30]. Our results may be due to the fact that stress management, rather than diabetes self-care per se, was the focus of the intervention.…”
Section: Discussionmentioning
confidence: 74%
“…The use of community health workers (CHWs) and their many variants (i.e, peer counselors, lay health workers, peer leaders, health advisors, promotoras ) have been shown consistently in RCTs to improve diabetes outcomes in Latinos. 43,44 CHWs are defined as “individuals who serve as bridges between their ethnic, cultural, or geographic communities and health care providers, and engage their community to prevent diabetes and its complications through education, lifestyle change, self-management and social support.” 44 While many CHW programs involve the use of phone calls for follow-up and reinforcement purposes, few integrate mobile health (mHealth) technology as a communication and informational channel between the patient, CHW, and health care team. CHWs have been used successfully in intensive telemonitoring and videoconferencing interventions in the home setting (i.e., The Informatics for Diabetes Education and Telemedicine (IDEATel) 45 ) and in the clinical setting (i.e., Promotoras-Telemedicine Care Provider Interaction Model 46 ).…”
Section: Merging the Community Health Worker Model And Ehealthmentioning
confidence: 99%
“…[1][2][3] As value-based payment models expand, providers will have more flexibility to fund CHWs with global budgets, or payers may elect to reimburse for CHW services. [4][5][6] The emerging evidence base on CHW programs 7 for the prevention and management of chronic diseases includes systematic reviews concluding that CHW interventions can improve overall health outcomes 8 and outcomes for patients with heart disease, stroke, 9 type II diabetes, [10][11][12] HIV, 13 and asthma 2,14 and for vulnerable patients with or at risk for a variety of chronic diseases or cancer. 15 Other systematic reviews have also documented the costs and cost-effectiveness of CHW programs, 15 but none, outside of low and middle-income countries, 16 have examined the impact of CHWs on the utilization of health services by patients with chronic conditions.…”
Section: Introductionmentioning
confidence: 99%